HUBUNGAN KECERDASAN EMOSIONAL DAN BUDAYA KERJA DENGAN KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN MEMPURA KABUPATEN SIAK - SUYUDI SUYUDI; KARTIKOWATI KARTIKOWATI; ZULKARNAIN ZULKARNAIN (Universitas Riau, 2017)
This study aims to investigate the relationship between the variables (1) ofemotional intelligence on the performance of teachers, (2) the culture of work on teacherperformance, (3) emotional intelligence and cultural work together on teacher performance.Respondents are public elementary school teachers in the district Mempura Siak totaling 107obtained by simple random sampling technique. Data collected through questionnaire as a researchinstrument. Analysis of the data used is descriptive analysis, inferential statistical analysis andhypothesis testing. Instrument reliability coefficient is calculated using Cronbach alpha. Partially,the results showed a positive relationship between emotional intelligence on the performance ofteachers by 0,303, and there is a positive relationship between workplace culture on teacherperformance of 0.347. While together is a positive relationship of emotional intelligence andworkplace culture on teacher performance amounted to 0,414.